Nasal glucagon: A new hope for severe hypoglycemia in type 1 diabetes - Heba, Salva; Parveen, Uzma; Khanum, Sara; Gulnaaz, Maaria; Tabassum, Maimuna; Safiyya, Syeda (Journal of Diabetes and Endocrine Practice, 2021)
Until now, injectable glucagon was the only available treatment used in the management of severe hypoglycemia wherein glucagon had to be prepared in several steps before administration. This method of delivery of injectable glucagon being cumbersome and unappealing for wide majority of the patients had led to a search for an alternative route of drug delivery. nasal glucagon (NG) now serves an efficient, safe, easy-to-administer, and a favorable substitute to glucagon injections. This ready to use device stand in clear contrast to overcome the limitations associated with the currently available glucagon preparations has emerged a key advancement in the management of severe hypoglycemia in adolescents and children with type 1 diabetes. NG is now being developed and studied in other countries as well to meet the unmet need for an easy and convenient glucagon administration. This review covers the basic information of nasal glucagon, trials on nasal glucagon in children and adults and its potential uses, limitations, and future scope in practice.
Keywords: Cumbersome; hypoglycemia; injectable glucagon; nasal glucagon; management